Bridging Cultures through Reflection: Metacognitive Approaches of Multicultural EFL Learners - Sukmawati Sukmawati; Syarifuddin Dollah (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2026)
This study aims to examine how EFL students from diverse cultural backgrounds manage their learning processes through metacognitive awareness and self-reflection in a multicultural academic setting. The importance of cross-cultural communicative competence in English language acquisition is increasing, rendering students' ability to regulate their cognition, learning strategies, and emotional responses crucial for achieving academic success. This study employed a phenomenological approach with eleven students from the English Language Education Study Program at Universitas Megarezky. Data were collected using semi-structured interviews and later analyzed using thematic analysis technique. The findings found four principal themes: Self-awareness, Strategic regulation, Cultural adaptation, and Competence transformation These findings emphasize the importance of integrating metacognitive and reflection-based learning practices into the EFL curriculum to enhance students' intercultural competence, emotional resilience, and learning independence. This research provides theoretical contributions to the study of metacognitive learning and cross-cultural communication, as well as practical implications for educators designing globally responsive English language learning.